Factors Behind the Changes in Canada's Family Income Distribution and the Share of the Middle Class - McWatters, Catherine; Beach, Charles (Relations industrielles / Industrial Relations)

(untitled) (Département des relations industrielles de l'Université Laval, 1990)
This paper seeks to examine whether there have been noticeable changes in the main features of the Canadian distribution of family income over the last two decades, in particular to examine what changes have occurred to the middle-class income share in Canada, and thence to identify possible determinants of these changes among a number of alternative hypotheses in the literature.